Análisis del proyecto minero “Cóndor Mirador”, ubicado en la parroquia Tundayme, cantón El Pangui, provincia de Zamora Chinchipe con respecto a los derechos de la naturaleza que garantiza la Constitución del Ecuador - Camacho Jadan., Fabricio Vicente (2024)
This Curricular Integration Work was carried out with the intention of providing a balanced and complete evaluation of environmental management in the parish of Tundayme, canton El Pangui, province of Zamora Chinchipe, in order to understand both the benefits and risks associated with the mining initiative, specifically focusing on the large-scale project "Condor Mirador". In this sense, to critically examine the effects of the project on the natural environment, local communities and the country's economy, it is proposed to contribute to increase public awareness of the challenges and opportunities associated with mining in Ecuador, providing the necessary guidelines that work as propositional exponents for the adoption of more responsible policies and practices in the mining sector. Within the framework of this study, a variety of research resources have been compiled, ranging from a wide selection of bibliographic references in digital and physical formats, to national and comparative legislation currently in force; likewise, various methodological approaches have been employed, among which are: scientific, deductive, analytical, exegetical, maieutic, statistical, synthetic and historical, in order to comprehensively address the topic in question. In line with the nature of the doctrinal research, the use of the documentary technique has been preferred as the most appropriate tool to understand the breadth of the theoretical ideas, as well as their limitations and scope, as they have been solidly supported and complemented by interviews with authorities linked to the case of analysis and who have been carefully selected according to their competences; These inputs have strengthened the understanding of the transcendence of good environmental practice and the importance of some social, ecological and economic axes, such as prior consultation, flora and fauna studies and labor openness within mining projects. These precedents set the basis for a concise analysis, supported by doctrine, national and international legislation, casuistry and accumulated experience. At the same time, this solid foundation has considerably enriched the discussion, allowing us to obtain a series of significant evaluations on the large-scale mining project "Condor Mirador" and at the same time, specific recommendations have been formulated that we trust will be fundamental for the future and will help to promote a positive and sustainable change in the mining industry.